A Breathing Zirconium Metal–Organic Framework with Reversible Loss of Crystallinity by Correlated Nanodomain Formation. Issue 10 (11th February 2016) - Bueken, Bart; Vermoortele, Frederik; Cliffe, Matthew J.; Wharmby, Michael T.; Foucher, Damien; Wieme, Jelle; Vanduyfhuys, Louis; Martineau, Charlotte; Stock, Norbert; Taulelle, Francis; Van Speybroeck, Veronique; Goodwin, Andrew L.; et al.
Abstract: The isoreticular analogue of the metal–organic framework UiO‐66(Zr), synthesized with the flexible trans ‐1, 4‐cyclohexanedicarboxylic acid as linker, shows a peculiar breathing behavior by reversibly losing long‐range crystalline order upon evacuation. The underlying flexibility is attributed to a concerted conformational contraction of up to two thirds of the linkers, which breaks the local lattice symmetry. X‐ray scattering data are described well by a nanodomain model in which differently oriented tetragonal‐type distortions propagate over about 7–10 unit cells. Abstract : Camouflaged from diffraction : The aliphatic isoreticular analogue of the well‐known MOF UiO‐66(Zr) undergoes a unique and reversible phase change upon guest removal. This change involves a topology‐dictated loss of long‐range order through the correlated formation of short‐range ordered nanodomains.